2005
DOI: 10.1145/1121812.1121821
|View full text |Cite
|
Sign up to set email alerts
|

A case study in efficient microcontroller education

Abstract: Abstract-Undergraduate education typically is characterized by a large number of students. Therefore, courses must be conducted efficiently and should not only focus on conveying the course material, but must also be oriented towards a maximum transfer of knowledge with a minimum amount of invested time on the instructor's part. At the same time, courses should be flexible to accommodate different student needs.In this paper 1 , we identify the needs of a practical course in microcontroller programming with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As pointed out in a number of research works [3,4,14,15,16], the introduction of hands-on experimental modules to science and engineering courses has a high impact on improving the educational outcome of the course. As an example, it is clearly shown in [16], and [17] how students performance can be improved by pairing programming and mechatronics teaching material with Arduino-based projects.…”
Section: Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out in a number of research works [3,4,14,15,16], the introduction of hands-on experimental modules to science and engineering courses has a high impact on improving the educational outcome of the course. As an example, it is clearly shown in [16], and [17] how students performance can be improved by pairing programming and mechatronics teaching material with Arduino-based projects.…”
Section: Workmentioning
confidence: 99%
“…In all the analyzed research work, some common key requirements can be identified for a teaching method that successfully implements physical computing and electronic concepts and integrates them with other STEM topics. Both at a high-school [3,4,18] and college [14,15,16] level all the studies pivot on the necessity of engaging students by removing unnecessary technical hurtles caused by overly complicated hardware and software tools, and on the necessity of having a unique flexible hardware and software framework where different concepts can be taught.…”
Section: Workmentioning
confidence: 99%
“…Weiss et al [14] have done a case study about the needs of a practical course in microcontroller programming. They have three concerns in their research, financial impact, educational impact and motivational impact, which can be conflicting when organizing a course.…”
Section: Related Workmentioning
confidence: 99%
“…Weiss et al [7] have done a case study about the needs of a practical course in microcontroller programming. They have three concerns in their research, financial impact, educational impact and motivational impact, which can conflict when organizing a course.…”
Section: Figure 1 Taxonomy Introduced By Fuller Et Al [3]mentioning
confidence: 99%